Harvesting European knowledge on soil functions and land management using multi‐criteria decision analysis. (12th April 2019) - Bampa, Francesca; O'Sullivan, Lilian; Madena, Kirsten; Sandén, Taru; Spiegel, Heide; Henriksen, Christian Bugge; Ghaley, Bhim Bahadur; Jones, Arwyn; Staes, Jan; Sturel, Sylvain; Trajanov, Aneta; Creamer, Rachel E.; et al.
Abstract: Soil and its ecosystem functions play a societal role in securing sustainable food production while safeguarding natural resources. A functional land management framework has been proposed to optimize the agro‐environmental outputs from the land and specifically the supply and demand of soil functions such as (a) primary productivity, (b) carbon sequestration, (c) water purification and regulation, (d) biodiversity and (e) nutrient cycling, for which soil knowledge is essential. From the outset, the LANDMARK multi‐actor research project integrates harvested knowledge from local, national and European stakeholders to develop such guidelines, creating a sense of ownership, trust and reciprocity of the outcomes. About 470 stakeholders from five European countries participated in 32 structured workshops covering multiple land uses in six climatic zones. The harmonized results include stakeholders' priorities and concerns, perceptions on soil quality and functions, implementation of tools, management techniques, indicators and monitoring, activities and policies, knowledge gaps and ideas. Multi‐criteria decision analysis was used for data analysis. Two qualitative models were developed using Decision EXpert methodology to evaluate "knowledge" and "needs". Soil quality perceptions differed across workshops, depending on the stakeholder level and regionally established terminologies. Stakeholders had good inherent knowledge about soil functioning, but several gaps were identified. In terms of critical requirements, stakeholders defined high technical, activity and policy needs in (a) financial incentives, (b) credible information on improving more sustainable management practices, (c) locally relevant advice, (d) farmers' discussion groups, (e) training programmes, (f) funding for applied research and monitoring, and (g) strengthening soil science in education.